The Effect of GCG on Company Profitability (Studies of Food and Beverage Companies Listed on The Indonesian Stock Market) 2014-2018) - et. al., Sendi Gusnandar Arnan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of good corporate governance on profitability in food and beverage companies listed on the Indonesia Stock Exchange for the period 2014 to 2018. The sample in this study is 14 financial reports. The research method used in this research is descriptive and explanatory methods. The sampling technique used in this study was non-probability sampling with a purposive sampling method. The data analysis used in this study was panel data regression analysis at a significance level of 5%. The program used in analyzing data uses the SPSS v20 program. The results showed that good corporate governance has an effect on profitability.